Visuomotor crowding: the resolution of grasping in cluttered scenes - Bulakowski, Paul F.; Post, Robert B.; Whitney, David (Frontiers in Behavioral Neuroscience, 2009)
Reaching toward a cup of coffee while reading the newspaper becomes exceedingly difficult when other objects are nearby. Although much is known about the precision of visual perception in cluttered scenes, relatively little is understood about acting within these environments—the spatial resolution of visuomotor behavior. When the number and density of objects overwhelm visual processing, crowding results, which serves as a bottleneck for object recognition. Despite crowding, featural information of the ensemble persists, thereby supporting texture perception. While texture is beneficial for visual perception, it is relatively uninformative for guiding the metrics of grasping. Therefore, it would be adaptive if the visual and visuomotor systems utilized the clutter differently. Using an orientation task, we measured the effect of crowding on vision and visually guided grasping and found that the density of clutter similarly limited discrimination performance. However, while vision integrates the surround to compute a texture, action discounts this global information. We propose that this dissociation reflects an optimal use of information by each system.